The Award of a Training Voucher and Labor Market Outcomes - Marie Paul; Annabelle Dörr; Bernd Fitzenberger; Thomas Kruppe; Anthony Strittmatter (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper estimates the labor market effects of being awarded with a training voucher using an instrumental variable approach. In Germany all public sponsored further training programs are allocated through vouchers and the system, we study here, thus represents a major case of the use of vouchers in the context of active labor market policies. We use process generated data in which we observe all training vouchers awarded in 2003 and 2004 as well as realized training participation. Results suggest that on average voucher recipients suffer from strong lock-in effects and only experience at best small positive employment effects and no earning gains four years after the award of the voucher. Subgroups of treated individuals, like individuals not holding a vocational degree and those participating in a degree program, benefit more.
Keywords: J68; C21; H43; 330